Evaluasi Tata Kelola Framework COBIT 5 pada Dinas Kependudukan dan Pencatatan Sipil - Liandi, Oki; Fitria, Fitria (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2019)
IT governance is needed to organize all factors and dimensions of information system to become synchronize. IT governance is expected to give additional values to an institution. Civil registry office in Tanggamus, Lampung for instance, in its information technology application was sometimes found the asynchronous population data. Thus, this research aimed to evaluate the IT governance on civil registry office in Tanggamus, Lampung. The methodology used in this research is operational audit using COBIT 5 framework due to its function in helping an institution gain a good IT governance. The result showed that IT governance in civil registry office in Tanggamus, Lampung was categorized in level 4, that is manage and measurable, which meant that the business process already well monitored and measured.